2013
DOI: 10.1111/bph.12225
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced endothelin receptor type B‐mediated vasodilation and underlying [Ca2+]i in mesenteric microvessels of pregnant rats

Abstract: BACKGROUND AND PURPOSENormal pregnancy is associated with decreased vascular resistance and increased release of vasodilators. Endothelin-1 (ET-1) causes vasoconstriction via endothelin receptor type A (ETAR), but could activate ETBR in the endothelium and release vasodilator substances. However, the roles of ETBR in the regulation of vascular function during pregnancy and the vascular mediators involved are unclear. EXPERIMENTAL APPROACHPressurized mesenteric microvessels from pregnant and virgin Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 93 publications
(134 reference statements)
6
37
0
Order By: Relevance
“…In addition, our previous studies in the aorta, carotid artery, and renal artery of virgin rats confirmed that ACh-induced relaxation was associated with increased NO production and was inhibited by the NOS inhibitor L-NAME (72). In contrast, in the mesenteric artery, a large portion of ACh-induced relaxation remained in the presence of L-NAME and the COX inhibitor indomethacin and was abolished by the K ϩ channel blocker TEA, suggesting a role of a hyperpolarization pathway (49,51). E 2 induces vasodilation through genomic and nongenomic endothelium-dependent and endothelium-independent pathways (53,64).…”
Section: Pregnancy-and E 2 /Er-related Adaptations In Vascular Functionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, our previous studies in the aorta, carotid artery, and renal artery of virgin rats confirmed that ACh-induced relaxation was associated with increased NO production and was inhibited by the NOS inhibitor L-NAME (72). In contrast, in the mesenteric artery, a large portion of ACh-induced relaxation remained in the presence of L-NAME and the COX inhibitor indomethacin and was abolished by the K ϩ channel blocker TEA, suggesting a role of a hyperpolarization pathway (49,51). E 2 induces vasodilation through genomic and nongenomic endothelium-dependent and endothelium-independent pathways (53,64).…”
Section: Pregnancy-and E 2 /Er-related Adaptations In Vascular Functionmentioning
confidence: 64%
“…We have previously reported differences in the sensitivity of the ACh relaxation response to the NOS blocker L-NAME, COX inhibitor indomethacin, and the hyperpolarization pathway in different vascular beds of virgin rats (72) and in mesenteric vessels of virgin versus pregnant rats (49). In the present study, we assessed the role of endothelial vasodilators in ER agonist-induced relaxation of blood vessels of pregnant rats.…”
Section: Bp Plasma E 2 Body Weight and Tissue Weightmentioning
confidence: 85%
“…Our laboratory has also shown that VSM contraction and [Ca 2ϩ ] i are reduced in renal arterial VSM cells of Preg rats (60). Also, endothelin-1-induced vasoconstriction and [Ca 2ϩ ] i are reduced in pressurized mesenteric microvessels of Preg compared with virgin rats (53). Although several studies have examined the pregnancy-related changes in arterial function and contraction mechanism, little is known regarding the changes in venous function during pregnancy.…”
Section: This Study Demonstrates Significant Reduction In Venous Funcmentioning
confidence: 98%
“…In addition, activation of protein kinase C (PKC) (30,38,42,80) or Rho kinase (ROCK) may play a role in the regulation of VSM contraction by increasing the [Ca 2ϩ ] i sensitivity of the contractile proteins (28,29,45,47,84). Several studies have also examined pregnancy-related changes in vascular reactivity in different arterial preparations from various species (15,17,31,36,41,53,60). Our laboratory has shown that aortic contraction is reduced in pregnant (Preg) compared with virgin rats (15,36,41,87).…”
Section: This Study Demonstrates Significant Reduction In Venous Funcmentioning
confidence: 99%
“…Whereas ETAR is known primarily for its role and expression in the underlying smooth muscle vascular layer in blood vessels, recent reports have highlighted its expression and function in endothelial cells as well, including a role in the secretion of ET1, regulation of intracellular calcium levels, and protective effects against hypoxia-induced cellular injury (1,4,25,39,41). Recently, a study examined the role of ETBR in pregnant rats, which observed enhanced ETBR-mediated microvascular relaxation compared with virgin rats (28). In a follow-up study, the same group used a rodent model of hypertensive pregnancy (reduction of uteroplacental perfusion pressure rats) and determined that ET1-induced constriction of microvessels was enhanced vs. normal pregnant rats, which was attributed to ETBR disruption/downregulation (29).…”
Section: A T 1 R E T a R E T B Rmentioning
confidence: 99%